Emerging Role of Sphingosine-1-phosphate in Inflammation, Cancer, and Lymphangiogenesis - Kazuaki Takabe (Biomolecules, 2013)
The main function of the lymphatic system is to control and maintain fluid homeostasis, lipid transport, and immune cell trafficking. In recent years, the pathological roles of lymphangiogenesis, the generation of new lymphatic vessels from preexisting ones, in inflammatory diseases and cancer progression are beginning to be elucidated. Sphingosine-1-phosphate (S1P), a bioactive lipid, mediates multiple cellular events, such as cell proliferation, differentiation, and trafficking, and is now known as an important mediator of inflammation and cancer. In this review, we will discuss recent findings showing the emerging role of S1P in lymphangiogenesis, in inflammation, and in cancer.